Green solvents for extractive separation of Pb(II) and Hg(II) from various resources-An update. (2022) - Panda, Itishree; Mishra, Sujata
Abstract: Heavy metals such as lead and mercury pollution are irreversible and stay for long time.The handling of wastes come out of industries, agriculture, domestic uses is very difficult to deal with. Hydro metallurgical technique like solvent extraction offers huge scope for the extraction, separation and purification of these waste materials in order to extract these metal values. The feasibility of ionic liquid as green solvents in the recovery of heavy metal ions like Pb(II) and Hg(II) from diverse resources are analyzed in this review. Ionic liquids, or salts having low melting temperature, have a number of benefits, including being long-lasting and environmentally friendly green solvents. Because of their specific attributes, like low vapour pressure, inflammability, less toxic character, appreciable ionic conductivity as well as a broad electrochemical potential window, these have got numerous application into diverse sectors, including hydro metallurgy. Despite the fact that a number of papers have been published on ionic liquids, pertinent research outcomes in the area of hydro metallurgical methods are very less. Due to the fact that investigation and use in this area are still in its early stages, more fundamental approaches to popularize these green solvents in the metal processing industries will be more challenging.Ammonium and phosphonium based ionic liquids have more stability than imidazolium based ionic liquids.Extraction process parameters like pH, time of extraction, extractant concentration, optimum temperature, volume ratio of both aqueous and organic phases in different extraction systems and their influences the extraction efficiency have been summarized.